2010
DOI: 10.2527/jas.2010-2865
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the existence of major genes affecting alpaca fiber traits1

Abstract: the World Wide Web at:The online version of this article, along with updated information and services, is located on www.asas.org at UOV / Biblioteca Universitaria on December 11, 2012 www.journalofanimalscience.org Downloaded from ABSTRACT: The aim of this study was to determine the presence of major genes for fiber diameter (FD), SD of FD (SDFD), CV of FD, and comfort factor (CF) in Huacaya (HU) and Suri (SU) Peruvian alpaca breeds. Bayesian segregation analyses with relaxed transmission probabilities were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
1
6
0
1
Order By: Relevance
“…The estimated additive genetic variances with the HE model (2.32) and the GR model (1.29) for the trait of fiber diameter were moderately less than those obtained before for the same population (with values of almost 3 or 4) as a consequence of an important change in the model with a more dissected residual effect. However, they were very close to the value of 1.71 found by Pérez-Cabal et al (2010) for the polygenic component when a model fitting a major gene was used, in contrast to the value of 3.19 when the major gene was not fitted. Difficulties in assigning variability caused by the major gene could be related to these differences between the Table 2.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The estimated additive genetic variances with the HE model (2.32) and the GR model (1.29) for the trait of fiber diameter were moderately less than those obtained before for the same population (with values of almost 3 or 4) as a consequence of an important change in the model with a more dissected residual effect. However, they were very close to the value of 1.71 found by Pérez-Cabal et al (2010) for the polygenic component when a model fitting a major gene was used, in contrast to the value of 3.19 when the major gene was not fitted. Difficulties in assigning variability caused by the major gene could be related to these differences between the Table 2.…”
Section: Discussionsupporting
confidence: 52%
“…Therefore, an important relationship seems to exist between these concepts, the mean value of the trait and its modification along the life span. Pérez-Cabal et al (2010) found evidence of the existence of a major gene for both fiber diameter and the SD of the trait in the same population. If both concepts are so narrowly related, it might be possible that a unique major gene could be influencing both traits.…”
Section: Discussionmentioning
confidence: 94%
“…The heritabilities found in this work showed that decreasing PM would be possible by artificial selection. These values were 0.225 and 0.237 for, respectively, PM and MFD for Huacaya genetic type, and 0.664 and 0.237 for Suri genetic type, suggesting the PM heritability in Suri genetic type the possible existence of a major gene segregating, maybe the same found for FD reported by Pérez-Cabal et al (2010). These values were similar than others estimated in other species, being 0.37 for PM in sheep (Sánchez et al, 2016), 0.23 in Angora goats (Allain and Roguet, 2006) and 0.29 in Argentinean lamas (Frank et al, 2011).…”
Section: Discussionmentioning
confidence: 51%
“…their animals 2011;Morante et al, 2009;Cervantes et al, 2010;Pérez-Cabal et al, 2010;Paredes et al, 2013), and has implemented a strict genetic selection on their animals looking for a desired proportional improvement of some determined traits. As a consequence, success has been globally observed both in the performances and in the genetic trends, but this success has not been obtained in the expected proportionality.…”
Section: Proportional Expected Genetic Responsesmentioning
confidence: 99%